Evaluating the impact of free trade zone construction on urban air pollution in China—Empirical evidence from a spatial differences-in-differences approach - Lou, Bailu; Xie, Baiwei; Liu, Peng; Zhu, Mingzi; Xu, Wangzi (Frontiers in Environmental Science, 2023)
The construction of China's Free Trade Zone (FTZ) is an important strategy for China's thorough deepening of opening up and achievement of long-term high-quality development. Based on the panel data of 283 prefecture-level and above cities in China from 2008 to 2019, this paper adopts the methods of Spatial Differences-in-Differences (SDID), Spatial Differences-in-Differences-in-Differences (SDDD), and spatial mediation effect test to empirically examine the impact and the spatial spillover of China's free trade zone on the environmental pollution of the pilot areas and its influencing mechanism. According to the findings of the study, the establishment of free trade pilot zones may cut urban PM2.5 emissions by roughly 2.9 percent, and FTZs can also greatly enhance the air quality of neighboring cities. Further examination of the influencing mechanism reveals that the establishment of an FTZ inhibits PM2.5 pollution and has a significant positive spillover effect on PM2.5 reduction in surrounding cities through the following means: attracting more foreign investment; improving the industrial structure and increasing the proportion of tertiary industry; prompting the local government to strengthen environmental regulation as part of the FTZ's supporting policies; Increasing investment in science and technology innovation, developing scientific and technological level to achieve green production. The empirical results of this paper are still robust after a series of robustness tests when the explained variable is replaced by the traditional air pollution indicator industrial nitrogen oxide emissions,another sort of spatial matrix is introduced, the propensity score matching SDID (PSM-SDID) and placebo tests as well as winsorize method are carried out. The inhibitory effect of FTZs on air pollution is modified by changes in city size, geographic location and city type, according to heterogeneity analysis. Finally, this paper proposes feasible policy recommendations.